1987
DOI: 10.1128/mcb.7.8.2700
|View full text |Cite
|
Sign up to set email alerts
|

Mutations affecting assembly and stability of tubulin: evidence for a nonessential beta-tubulin in CHO cells.

Abstract: Eight strains of Chinese hamster ovary (CHO) cells having an assembly-defective ,-tubulin were found among revertants of strain Cmd 4, a mutant with a conditional lethal mutation in a 0-tubulin gene (F. Cabral, M. E. Sobel, and M. M. Gottesman, Cell 20:29-36, 1980). The altered j3-tubulins in these strains have electrophoretically silent alterations or, in some cases, an increase or a decrease in apparent molecular weight based on their migration in two-dimensional gels. The identity of these variant proteins … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
28
0

Year Published

1995
1995
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 22 publications
4
28
0
Order By: Relevance
“…The latter method also detected an increased expression of ␣-tubulin that may reflect coordinate regulation of the intracellular levels of ␣-and ␤-tubulin as has been suggested previously (52). Alternatively, it may be that either qualitative or quantitative alterations in ␣-tubulin can in their own right contribute to the taxol-resistant phenotype.…”
Section: ␤-Tubulin Isotypes In Taxol-resistant Cellssupporting
confidence: 73%
“…The latter method also detected an increased expression of ␣-tubulin that may reflect coordinate regulation of the intracellular levels of ␣-and ␤-tubulin as has been suggested previously (52). Alternatively, it may be that either qualitative or quantitative alterations in ␣-tubulin can in their own right contribute to the taxol-resistant phenotype.…”
Section: ␤-Tubulin Isotypes In Taxol-resistant Cellssupporting
confidence: 73%
“…In this process, many genes were lost or became haploid (Siminovitch, 1976). In addition, we have shown that CHO cells produce a surfeit of tubulin and can lose half of their ␤1-tubulin (35% of total ␤-tubulin) with no apparent effect on growth of the cells (Boggs and Cabral, 1987). Yet, the low percentage of ␤5-tubulin has persisted, suggesting that this isotype may play a vital role in microtubule assembly.…”
Section: Discussionmentioning
confidence: 99%
“…3 Protein translation was then inhibited for different periods of time using cyclohexamide, following which the cells were lysed, and levels of the transfected proteins were determined by Western blotting. As a control, we also measured the levels of ␣-tubulin, which has a half-life of greater than 40 h (25). In these assays, we observed that Net1A expressed together with GFP exhibited a half-life of 0.35 h (Fig.…”
Section: Rna Interference-mediated Inhibition Of Dlg1 Expression Redumentioning
confidence: 99%